Retention of allied health professionals in rural New South Wales: a thematic analysis of focus group discussions - Keane Sheila; Lincoln Michelle; Smith Tony (BMC, 2012)
Abstract Background Uneven distribution of the medical workforce is globally recognised, with widespread rural health workforce shortages. There has been substantial research on factors affecting recruitment and retention of rural doctors, but little has been done to establish the motives and conditions that encourage allied health professionals to practice rurally. This study aims to identify aspects of recruitment and retention of rural allied health professionals using qualitative methodology. Methods Six focus groups were conducted across rural NSW and analysed thematically using a grounded theory approach. The thirty allied health professionals participating in the focus groups were purposively sampled to represent a range of geographic locations, allied health professions, gender, age, and public or private work sectors. Results Five major themes emerged: personal factors; workload and type of work; continuing professional development (CPD); the impact of management; and career progression. 'Pull factors' favouring rural practice included: attraction to rural lifestyle; married or having family in the area; low cost of living; rural origin; personal engagement in the community; advanced work roles; a broad variety of challenging clinical work; and making a difference. 'Push factors' discouraging rural practice included: lack of employment opportunities for spouses; perceived inadequate quality of secondary schools; age related issues (retirement, desire for younger peer social interaction, and intention to travel); limited opportunity for career advancement; unmanageable workloads; and inadequate access to CPD. Having competent clinical managers mitigated the general frustration with health service management related to inappropriate service models and insufficient or inequitably distributed resources. Failure to fill vacant positions was of particular concern and frustration with the lack of CPD access was strongly represented by informants. Conclusions While personal factors affecting recruitment and retention of allied health study participants were similar to doctors, differences also existed. Allied health professionals were attracted by advanced work roles in a context of generalist practice. Access to CPD and inequitable resource distribution were strong 'push' factors in this group. Health policy based on the assumption of transferability between professions may be misguided.